STRATEGIES FOR INTEGRATING DERIVATIVE FINANCIAL INSTRUMENTS INTO UZBEKISTAN'S ECONOMIC POLICY (International journal of artificial intelligence, 2025)
This article analyzes the strategies for integrating derivative financial instruments (futures, options, swaps) into Uzbekistan's economic policy. It highlights the contribution of derivatives to financial stability, risk management, and the deepening of the capital market. Based on the current legislative framework, infrastructure, and level of financial literacy in the country, the stages of their implementation into the economic system are reviewed. The article also offers integration strategies based on international experience, regulatory approaches, and forward-looking recommendations.